PRARANCANGAN PABRIK SODIUM KARBOKSIMETIL SELULOSA DARI SELULOSA DAN ASAM MONOKHLOR ASETAT DENGAN KAPASITAS 8000 TON/TAHUN - , RISQI PUTRI NUR PRIATMA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sodium carboxymethyl cellulose plant is designed for a capacity 8.000 tons/year. The material needed are cellulose 339,7218 tons/year, monochloroacetic acid 204,5802 tons/year, and NaOH 89,1990 tons/year. Sodium carboxymethyl cellulose is produced by process steps include alkalization, carboxymethylation, and purification. The main process is carboxymethylation that a reaction between cellulose with sodium monochloroacetat into sodium carboxymethyl cellulose. This reaction occured in rotary reactor at temperature 30-70Â°C and pressurre of 1 atm. This reaction is exothermic. The product of the reaction is ripened in the aging bin in 8 hours. Then the size of the product is reduced in ball mill. Then the product is dryed in rotary dryer. Product sodium carboxymethyl cellulose has a purity of 68%. Sodium carboxymethyl cellulose plant will be built in Cilegon, Banten with area 40.700 m2. The amount of the labours is 248 people. Utilities needed are make up water of 12.220,35 kg/hour, electricity of 945,1284 kW, compressed air of 150 m3/hour, and steam of 7.620,79 kg/hour. This plant is classified low risk. The fixed capital investment is $ 7,715,084.05 + Rp 144.421.131.600,00 and working capital is $ 1,162,445.29 + Rp 39.731.508.700,00. Manufacturing cost is $ 5,882,046.59 + Rp 114.390.621.200,00